The Functions and Mechanisms of PR-DUB in Malignancy - Cao, Lei; Li, Rui; Wu, Xudong (Frontiers in Molecular Biosciences, 2021)
The interplay between cancer genome and deregulated epigenomic control is critical for cancer initiation and progression. ASXL1 (Additional Sex combs-like 1) is frequently mutated in tumors especially myeloid malignancies. However there remains a debate whether the mutations are loss or gain-of-function. Mechanistically, ASXL1 forms a complex with BAP1 for the erasure of mono-ubiquitylation at lysine 119 on Histone H2A (H2AK119ub1), a well-known histone mark associated with transcription repression. Unexpectedly, this de-ubiquitylation complex has been genetically defined as a Polycomb Repressive complex (PR-DUB) though the regulatory mechanisms are elusive. In this review, we will discuss about the functions of ASXL1 in malignancies and reconcile seemingly paradoxical effects of ASXL1 or BAP1 loss on transcription regulation.